2019
DOI: 10.1080/0142159x.2019.1605161
|View full text |Cite|
|
Sign up to set email alerts
|

Use of evidence in health professions education: Attitudes, practices, barriers and supports

Abstract: Introduction: Health professions educators are increasingly called upon to apply an evidence-informed approach to teaching and assessment practices. There is scant empirical research exploring educators' attitudes, practices, and perceived barriers and supports to using research evidence in educational practice. Methods: We conducted a survey of AMEE members to explore three domains related to evidence-informed health professions education: (1) attitudes; (2) practices; and (3) supports and barriers. Analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 34 publications
3
23
1
Order By: Relevance
“…These contextual factors include having access to appropriate tools, faculty development and a local culture aligned with principles of assessment for learning, as also highlighted recently in Griffith et al 9 These findings also mirror the work by Thomas et al 78 and…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These contextual factors include having access to appropriate tools, faculty development and a local culture aligned with principles of assessment for learning, as also highlighted recently in Griffith et al 9 These findings also mirror the work by Thomas et al 78 and…”
Section: Discussionsupporting
confidence: 76%
“…9 These barriers are in line with those reported in emerging research in other areas of HPE exploring the factors that support or hinder Evidence Informed HPE. 77,78 In some instances, what was seen as a barrier could also be -in different contexts or under different circumstances -a facilitator.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns have emerged over time that there may be a knowledge translation problem in medical education [12][13][14][15][16] with this gap between research and practice having been identified in the medical education literature. [17][18][19] Indeed, our results are not dissimilar from a single centre study conducted by Nelson and et al almost 30 years ago, 20 where none of 14 medical school pre-clinical course directors were familiar with any current education research. The authors found that the course directors did not find medical education research particularly relevant to their teaching.…”
Section: Discussioncontrasting
confidence: 51%
“…The process of the curriculum integration and change may be greatly enhanced by the EIHPE approach. 15 This process demands changes on both organizational and individual levels, dedication of time for faculty development, financial and educational resources, energy, expertise, and support from educational leadership (e.g., deans and their academic team). 16,17 Understanding the context of the environment in which the changes will occur is also an essential step, along with the effective communication between faculty in the different departments involved in cariology education (e.g., basic sciences, restorative dentistry, pediatric dentistry).…”
Section: Discussionmentioning
confidence: 99%
“…The process of the curriculum integration and change may be greatly enhanced by the EIHPE approach 15 . This process demands changes on both organizational and individual levels, dedication of time for faculty development, financial and educational resources, energy, expertise, and support from educational leadership (e.g., deans and their academic team) 16,17 .…”
Section: Discussionmentioning
confidence: 99%